2021
DOI: 10.4103/jehp.jehp_481_20
|View full text |Cite
|
Sign up to set email alerts
|

Effects of COVID-19 pandemic lockdown on medical advice seeking and medication practices of home-bound non-COVID patients

Abstract: BACKGROUND: Many countries are implementing measures for social distancing to contain the spread of the coronavirus disease 2019 (COVID-19) pandemic. The Indian government also issued an order for complete lockdown of the country, with all the nonessential services, including most of the services for nonemergency health issues, being temporarily suspended. OBJECTIVES: This study aimed to understand the effect of pandemic lockdown on medical advice-seeking behavior and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 7 publications
0
24
0
2
Order By: Relevance
“…There was, however, an early downturn followed by a rapid increase in hospitalized non-COVID-19 patients with PE which deserves attention. The population may have been reluctant to seek medical care during the early phase of the pandemic and lockdown (in March) due to public health policy and fear of contamination [ 30 ]. It could also be a delayed effect of the restrictions and lockdown.…”
Section: Discussionmentioning
confidence: 99%
“…There was, however, an early downturn followed by a rapid increase in hospitalized non-COVID-19 patients with PE which deserves attention. The population may have been reluctant to seek medical care during the early phase of the pandemic and lockdown (in March) due to public health policy and fear of contamination [ 30 ]. It could also be a delayed effect of the restrictions and lockdown.…”
Section: Discussionmentioning
confidence: 99%
“…About half of individuals with medical illnesses handled their conditions by calling doctors through telemedicine and collecting their own medication from a community pharmacy. Previous studies revealed that around 55% of patients with chronic diseases did not contact their doctors and depended on self-medication [ 33 , 34 ]. In concordance with our findings, previous studies showed that people have generally been practicing—or have been pushed to practice—rational medical practices in the face of the greater concern consuming their minds regarding the pandemic and the risks of contracting it by venturing outside.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of participants with medical illnesses controlled their tolerable suffering by following the medications already provided or by calling doctors as necessary. Only a true emergency (fracture) or a perceived emergency (illness) had prompted the travel to a medical facility away from home (suspected COVID-19) [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tandon e cols. (2021), explicaram que na pesquisa envolvendo 312 pessoas, apenas um participante fez uso de hidroxicloroquina por conta própria, como medida profilática contra a COVID-19 (17), como observado também no estudo de Quispe-Cañari e cols. (2021) (15).…”
Section: Zhang E Cols (2021) Austrália (19)unclassified
“…A hidroxicloroquina foi discutida na Índia como uso profilático na prevenção e tratamento da COVID-19, no entanto o governo explicou e recomendou a sua não utilização (17). Outros estudos informaram que não há tratamento, uma vez que não existe comprovação científica que assegure a eficácia no tratamento e profilaxia, assim como da cloroquina.…”
Section: Zhang E Cols (2021) Austrália (19)unclassified